Factors Associated with Exclusive Breastfeeding in a Maternity Hospital Reference in Humanized Birth - Gabriela Pinheiro Brandt; Alan Messala A. Britto; Camila Carla De Paula Leite; Luciana Garangau Marin
Abstract Objective To analyze the factors associated with the prevalence of exclusive breastfeeding (EBF) for up to six months in mother/infant binomials cared for at a usual-risk maternity hospital. Methods The present is a descriptive, longitudinal, prospective, quantitative study. Socioeconomic, obstetric and perinatal variables from 101 mother/infant binomials in a Public Maternity Hospital in the city of Curitiba, state of Paraná, Brazil, were investigated during hospitalization after delivery and 6 months after birth. For the statistical analysis, the Chi-squared test was used. The variables that showed values of p < 0.25 for the Chi-squared test were also submitted to an odds ratio (OR) analysis. Results The prevalence (42.6%) of EBF was observed. Most women (93.1%) had had more than 6 prenatal consultations, and the variables maternity leave and support to breastfeeding were associated with EBF. Support to breastfeeding by professionals and family members increased 4-fold the chance of maintenance of EBF (OR = 0.232; 95% confidence intercal [95%CI]: 0.079 to 0.679; p = 0.008). Cracked nipples were the biggest obstacle to breastfeeding, and low milk production was the main responsible factor for weaning. Conclusion The encouragement of breastfeeding and the mother's stay for a longer period with the child contributed to the maintenance of EBF until the sixth month of life of the infant.